EFFECT OF POTASSIUM HUMATE ON SEED GERMINATION, SEEDLING GROWTH AND VEGETATIVE CHARACTERS OF Triticum aestivum (L.) cv. LOKVAN - R.B. PATIL; S.S.MOKLE; S.S. WADJE (International Journal of Pharma and Bio Sciences, 2010)
A Laboratory experiment was conducted to study the effect of potassium humate (salt of humic acid) on seed germination and seedling growth (root length and shoot length) of Triticum aestivum (L.) cv. Lokvan. The seeds of Triticum aestivum were treated with potassium humate at ten different concentrations (from 0.1 to 1.0%) and water served as control. The seeds were then sown on moist blotter papers and percent seed germination, root length and shoot length of Triticum aestivum were recorded. In order to see the effect of potassium humate (1.0%) on vegetative characters of Triticum aestivum, pot experiments were conducted. At the end of tenth day, potassium humate treated seeds showed positive correlation between concentration of potassium humate and percent seed germination with root length and shoot length of Triticum aestivum against water (control). Regarding the vegetative characters of plants, potassium humate treated plants showed more vegetative growth than control plants (untreated plant).